P027 Repertoire analysis of memory T-cell receptors in Japanese patients with inflammatory bowel disease. (15th January 2020) - Takeru, N; Kakuta, Y; Izumiyama, Y; Ichikawa, R; Okamoto, D; Moroi, R; Kuroha, M; Kanazawa, Y; Kinouchi, Y; Masamune, A
Abstract: Background: The T-cell receptor (TCR) repertoire was assessed in response to various antigens and was considered to be associated with the pathogenesis of inflammatory bowel disease (IBD). Thus, we performed TCR repertoire analysis to examine the pathology of IBD from changes in the TCR repertoire of memory T cells in the intestinal lamina propria mononuclear cells (LPMCs) and peripheral blood mononuclear cells (PBMCs) of patients with IBD. Methods: LPMCs in the surgical specimens and PBMCs were isolated from 12 patients with IBD [five patients with ulcerative colitis (UC) and seven patients with Crohn's disease (CD)]. PBMCs were collected from 10 healthy individuals as controls. Comprehensive TCR sequence analyses of adaptor-ligation PCR products were performed using MiSeq. Results: The diversity of TCR-α and -β in PBMCs was significantly lower in patients with IBD than that in controls ( p = 0.00084 and 0.0013, respectively). Comparisons of TCR diversity in LPMCs and PBMCs between CD and UC showed that the diversity in LPMC was not affected by diseases, whereas that in PBMCs was significantly lower in CD than in UC ( p = 0.045 and 0.049, respectively). Some TCR clones may have shown a specific increase or decrease in CD and UC and many clones were common to both LPMCs and PBMCs in the same patients. Conclusion: The diversity of TCR clones in LPMCs and PBMCs in patients with IBD was significantly lower than that of PBMCs in controls. TCR diversity in PBMCs was particularly low in patients with CD.